2001
DOI: 10.1007/s00268-001-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastases of Gastroenteropancreatic Neuroendocrine Tumors: Safe Hepatic Surgery

Abstract: Liver metastases of neuroendocrine tumors are usually slow-growing, and cytoreductive hepatectomy can help reduce the effects of endocrinopathies and increase life expectancy and symptom-free survival. However, it has yet to be fully investigated how hepatectomy for metastatic neuroendocrine tumors can be performed safely. Here we report the results of 13 patients with neuroendocrine liver metastases operated on in our institution and those of a French multicentric study that included 131 patients. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 19 publications
1
46
0
3
Order By: Relevance
“…However, the overall survival after hepatic resection has been reported in 46-86% at 5 years and 35-79% at 10 years (49,59,60,61,62,63,64,65,66,67,68,69,70,71,72). This wide heterogeneity reflects the selection bias that is present in the majority of series.…”
Section: Surgery Of Lmmentioning
confidence: 99%
“…However, the overall survival after hepatic resection has been reported in 46-86% at 5 years and 35-79% at 10 years (49,59,60,61,62,63,64,65,66,67,68,69,70,71,72). This wide heterogeneity reflects the selection bias that is present in the majority of series.…”
Section: Surgery Of Lmmentioning
confidence: 99%
“…Methods of measurement of the future remnant vary, 7 but most investigators propose that preoperative PVE is indicated when the measured future liver remnant volume is expected to be less than 25% to 45% of the preoperative functional liver volume (FLV) [8][9][10][11][12] or when the standardized FLV will be less than 1% of the patient's body weight (BW). 13 Recognition that these criteria have been determined empirically 7 and that the benefits of PVE may not be as obvious for patients with normal underlying liver as for patients with chronic liver disease 14,15 has led to increased interest in better definition of the indications for PVE and clearer determination of the limits of safe resection in patients with normal liver.…”
mentioning
confidence: 99%
“…Nevertheless, according to recent studies, less than 15 % of patients presenting with metastatic disease are eligible for a debulking procedure [59,62] as no survival advantage has been shown in patients receiving suboptimal debulking (<90 % of disease burden) [62][63][64]. Unfortunately, even after removal of all metastatic disease with microscopic negative margin (R0), the recurrence (or persistence) rate remains high with 1-year and 5-year disease free survival (DFS) of 53.7 and 10.7 %, respectively [23].…”
Section: Advanced Diseasementioning
confidence: 99%